Favorable remodeling after hybrid arch debranching and modified provisional extension to induce complete attachment technique in type a aortic dissection: A case report - Kazimierczak, Arkadiusz (Medicine (Baltimore), 2018)
RATIONALE: Type A aortic dissection (TAAD) usually requires emergency open repair of the ascending aorta. In cases of diffuse dissection that spreads along the descending and abdominal aorta (type I, DeBakey classification), the risk of aneurysmal degeneration varies between 30% and 50% during 5 years and increases even higher during a longer follow-up. Those patients might require complex intervention to prevent aortic rupture. A combination of hybrid arch debranching and the extended provisional extension to induce complete attachment (e-PETTICOAT) technique might be an available alternative in such cases. This is the first report of the successful use of the e-PETTICOAT technique for treating degenerative, diffuse TAAD. PATIENT CONCERNS: Acute chest pain and syncope were the initial symptoms of diffuse TAAD in our 66-year-old female patient. Open replacement of the ascending aorta followed by surgical arch debranching was performed as a staged procedure. Unfortunately, progressive aneurysmal degeneration was revealed 6 months later in the thoracic, abdominal, and infrarenal aorta with the recurrence of chest and lumbar pain. DIAGNOSES: Computed angiotomography revealed severe aneurysmal degeneration of aortic dissection in the thoracic and abdominal aorta. INTERVENTION: The e-PETTICOAT enabled good remodeling and stopped degeneration. OUTCOME: At the 2-year follow-up, good remodeling with complete false lumen thrombosis and a stable aortic size were confirmed. LESSON: Lifelong follow-up in extensive TAAD should be considered. The e-PETTICOAT technique is an available alternative to fenestrated endovascular aortic repair for degenerative TAAD, as it promotes favorable remodeling after successful surgery of the ascending aorta.